Optical, Thermal, and Mechanical Properties of L-Serine Phosphate, a Semiorganic Enhanced NLO Single Crystal. (24th February 2016) - Rajesh, K.; Mani, A.; Thayanithi, V.; Kumar, P. Praveen
Abstract : Single crystals of L-serine phosphate (LSP) were grown by slow evaporation technique. The optical studies reveal the transparency of the crystal in the entire visible region. Grown crystal was subjected to single crystal XRD diffraction technique. Thermal studies of LSP confirm the thermal stability of the crystal and it is stable up to 210°C. The functional groups and optical behaviour of the crystal were identified from FT-IR and UV-Vis analysis. The crystals were also characterized by microhardness and photoconductivity to determine the mechanical strength and the optical conductivity. Laser damage threshold and nonlinear optical activity of the grown crystal were confirmed by Q-switched Nd : YAG laser beam.